Mittelalter in der größeren Welt Essays zur Geschichtsschreibung und Beiträge zur Forschung - Borgolte, Michael 1948- (Europa im Mittelalter, 2014)
The fall of the Berlin Wall in 1989 and globalization have forced national history to yield place to European and global history. In medieval studies, Michael Borgolte has taken up the new challenge as no other German historian, encouraging the development of transcultural research on the Middle Ages. This volume includes several of his essays, but is intended to serve more as the basis for further research rather than to take stock of his work